Di-tert-butyl peroxide as an effective two-carbon unit in oxidative radical cyclization toward 7-methylazolo[1, 5-a]pyrimidines. Issue 11 (28th April 2022) - Gao, Qinghe; Sun, Zhenhua; Wu, Manman; Guo, Yimei; Han, Xinya; Yan, Jufen; Ha, Minh Ngoc; Le, Quynh Mai; Xu, Yongtao
Abstract : An unexpected oxidative radical cyclization with DTBP as the C2 cyclic unit enables the assembly of privileged 7-methylazolo[1, 5- a ]pyrimidines. Abstract : An unexpected oxidative radical cyclization of 3(5)-aminoazoles and aromatic aldehydes with di- tert -butyl peroxide (DTBP) is described. This established protocol enables the assembly of privileged 7-methylpyrazolo[1, 5- a ]pyrimidines as well as 7-methyl-[1, 2, 4]triazolo[1, 5- a ]pyrimidines with excellent regioselectivity and functional group tolerance, where DTBP firstly emerges as the C2 cyclic unit rather than the usual methyl radical source. The reaction is further highlighted by the late-stage modifications of natural products and pharmaceuticals.